2023
DOI: 10.1111/ijfs.16325
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of bioactive components and evaluation of microbial community and antibacterial activity from Heterotrigona itama and Tetrigona binghami honeys

Abstract: Summary Stingless bee honey is a precious food product with therapeutic benefits. In this study, we determined the quality of Malaysian stingless bee honeys (Heterotrigona itama and Tetrigona binghami) by the physicochemical characteristics, phenolic compounds, and organic acids. Our results revealed that the major phenolic compounds in all honey samples were chlorogenic acid and myricetin, and the major organic acids contained gluconic acid and trans‐cinnamic acid. The microbial community in honeys characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…(2019) reported two Bacillus sp., Wu et al . (2023) recorded significant abundance of Lactobacillus and Goh et al . (2021) isolated lactic acid bacteria in Kelulut honey from Sabah.…”
Section: Introductionmentioning
confidence: 99%
“…(2019) reported two Bacillus sp., Wu et al . (2023) recorded significant abundance of Lactobacillus and Goh et al . (2021) isolated lactic acid bacteria in Kelulut honey from Sabah.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they are the natural source of ingredients in foodstuffs (Kose & Ocak, 2018). Most studies have shown that phenolic compounds in plants contribute significantly to their antioxidant capacity (Cai et al ., 2004; Wu et al ., 2023; Shan et al ., 2007; de Andrade et al ., 2022). Some studies have shown that phenolic compounds found in plants may also play a characteristic as antimicrobial role (Hara‐Kudo et al ., 2004; Huang et al ., 2023; Wu et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have shown that phenolic compounds in plants contribute significantly to their antioxidant capacity (Cai et al ., 2004; Wu et al ., 2023; Shan et al ., 2007; de Andrade et al ., 2022). Some studies have shown that phenolic compounds found in plants may also play a characteristic as antimicrobial role (Hara‐Kudo et al ., 2004; Huang et al ., 2023; Wu et al ., 2023). These plants, which have high antioxidant effects, can be used to prevent oxidation and to preserve foods, and may also be used in the treatment of diseases (Negara et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%